An exploratory study into the development and effectiveness of an Interaction and Communication for Engagement (ICE) Framework for children showing attention difficulties in learning - Griffiths, Lise (2020)
Teachers can feel children with attention difficulties present a particular challenge to teach (Kos et al. 2006). Children with these difficulties can struggle to maintain engagement in academic classroom activities, rather than sensory or imaginative (e.g. Imeraj et al. 2013) but may be effectively engaged using interaction and communication principles (e.g. Stevens et al. 2000). A comprehensive intervention approach refining interaction and communication, enhancing academic learning engagement of children showing attention difficulties could be low cost and high impact, and contribute to early intervention.